Humoral immune response after anti-SARS-CoV-2 vaccine “booster” dose in patients with monoclonal gammopathy of undetermined significance (MGUS) - NICOLA SGHERZA; Paola Curci; Rita Rizzi; Angela Maria Vittoria Larocca; Luigi Vimercati; Silvio Tafuri; Maria Chironna; Pellegrino Musto (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Not Applicable.